The Function Of Ngenteg Linggih Ceremony In Pejaten Tabanan - Ida Ayu Tary Puspa; Ida Bagus Subrahmaniam Saitya (Jayapangus Press, 2021)
The Dewa Yajña Ceremony is a ceremony addressed to Ida Sang Hyang Widhi with all of His manifestations as a form of devotion because He has created the universe and everything in it. This gratitude was manifested by the people of Pejaten Village by holding a ceremony to instill the Creator to rest in the sacred temple building. The Ngenteg Linggih ceremony has functions such as religious, ethics, aesthetics, and social. Each of these functions is related to one another which of course will play a role in the ceremony. Such as a religious function in which the ceremony provides a basis for belief in the community through the rites and ritual equipment to convince the public that through the ceremony carried out, religious emotions will grow. The function of ethics is to provide guidance in living through the Ngenteg Linggih ceremony to always live life by thinking, saying, and doing good according to what you are doing in your ceremony. The aesthetic function provides beauty as well as truth and sanctity so that people feel the beauty in regulating life practices as outlined in the means and implementation of the ceremony. The social function is shown by the community who work together hand in hand to load the ceremony and carry it out with the concept of ngayah.